Principles of effective out-patient diagnostics of diffuse liver diseases - Komova A. G.; M. V. Mayevskaya; V. T. Ivashkin (Российский журнал гастроэнтерологии, гепатологии, колопроктологии)
Aim of investigation. To study prevalence of diffuse liver diseases in the Russian Federation by the example of large industrial city with application of screening tests. Material and methods. Overall 5000 Moscow inhabitants age 18 to 75 years, chosen randomly within the «the liver check up» project, have been included in prospective population study. All patients underwent following investigation: physical examination, filling of nutrition diary, CAGE and AUDIT questionnaires, taking occupational history, anthopometrical examination, US of abdominal organs, clinical and biochemical blood tests, assessment of HCVAb and HBsAg. In the case of abnormal liver tests preliminary diagnosis was determined according to certain algorithm and these patients were recruited for further investigation and specifications of diagnosis in department of hepatology, University clinical hospital N 2, State educational government-financed institution of higher professional education «Sechenov First Moscow state medical university». Results. Abnormal liver functional tests were revealed in 30,6% of industrial city inhabitants — in 1461 of 4768 cases (232 patients were excluded from the study due to partial data loss), significantly more frequently in men in comparison to women, i.e. 49,7 and 25,5% respectively (p<0,001). Prevalence of diffuse liver diseases in the studied sample (n=4768) was following: non-alcoholic fatty liver disease —7,4% (n=352), alcohol-induced liver disease — 6,9% (n=329), hepatitis C — 6,7% (n=322), hepatitis B — 1,9% (n=91), drug-induced liver disease — 0,82% (n=39), cholestatic liver diseases — 0,69 % (n=33), autoimmune hepatitis — 0,78% (n=37), others — 5,4% (n=258). Conclusion. Risk factors for diseases, defined by one-way ANOVA test, were: male gender (p<0,001), excessive body weight and obesity (body mass index >25 kg/m2 (p<0,001)), hyperglycemia (p<0,001), hypertriglyceridemia (p<0,001). By more strict estimation at multifactorial analysis major risk factors were determined: age 30 to 59 years (p<0,001), intake of alcoholic beverages in harmful dozes (over 16 points of AUDIT questionnaire, p=0,04), hypercholesterolemia (p=0,016). Relative weight of those, requiring etiological and pathogenic treatment after specification of preliminary diagnosis, of patients with abnormal liver tests, revealed at screening stage, was 80,3%.